Pengenalan Tindakan Anti Bullying pada Siswa di SDN 1 Plumbon - Fickry Nur Farhansyah; Vidiyanti Vidiyanti; Silvia Dwi Putri; Meita Landivah; Dwi febiyolah; Jamilah Jamilah; Apriyanto Apriyanto; Trio Adi Kusuma; Iin Mintarsih; Mimin Darmini (Mathematics Education Study Program, 2025)
Bullying in the elementary school environment is a serious problem that requires comprehensive handling. Observations conducted at SDN 1 Plumbon revealed that verbal bullying and the tendency of physical violence are the main problems at SDN 1 Plumbon. This study aims to introduce bullying at SDN 1 Plumbon. The activity was carried out through an extension approach with a socialization method involving material delivery, educational video screening, and interactive discussions. The program was conducted in three stages on 1-3 November 2024, targeting all students from grades 1 to 6. Results showed that in the first stage (grades 1-2), despite challenges in classroom management, students showed high enthusiasm for the material presented. In the second phase (grades 3-4), the activities ran smoothly with an active level of participation in discussions, signaling the achievement of learning objectives. The third stage (grades 5-6) showed students' deep understanding of the impact of bullying, demonstrated through serious responses during video playback and active sharing of experiences and solutions. This activity resulted in increased student awareness about the dangers of bullying and the importance of creating a safe school environment. The students also showed a commitment to prevent bullying and become advocates for friends who are victims. This gradual socialization approach proved effective in instilling an understanding of bullying prevention at the elementary school levell